The Effect of Organizational Justice and Organizational Commitment on Teacher Performance with Job Satisfaction as a Mediator in Private Elementary Schools - Mukti, Kiki Trisna; Basrowi; Khaeruman (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2024)
The purpose of this study is to determine the influence of organizational justice and organizational commitment on teacher performance with job satisfaction as a mediator in Cilegon City Private Elementary School. In this study, a quantitative method is used, where variables are measured using a Likert scale. The data collection method was carried out by distributing questionnaires. The population in this study is private elementary school teachers in Cilegon City. The sample used in this study amounted to 200 respondents. The analysis tool used in this study uses Smartpls v.3.2.9 software. Based on the results of the data analysis, it can be concluded that (1) organizational justice has a positive and significant effect on teacher performance, (2) organizational commitment has a positive and significant effect on teacher performance, (3) organizational justice has a positive and significant effect on job satisfaction, (4) organizational commitment has a positive and significant effect on job satisfaction, (5) job satisfaction has a positive and significant effect on teacher performance, (6) job satisfaction can mediate the relationship between organizational justice and performance (7) job satisfaction can mediate the relationship between organizational commitment and teacher performance significantly.